PERANCANGAN DAN PENGUKURAN KINERJA GUDANG BAHAN BAKU DI PT.XYZ , SIDOARJO - Aji Limantoro; Markus Hartono; Amelia Santoso (CALYPTRA, 2018)
This paper is discussing about PT. XYZ shoes warehouse performance improvement. Performance improvement start from measuring company performance using “scorecard”. Scorecard design is used for performance improvement using 3 perspectives including: receiving, storage, and order picking. Performance criteria for all perspectives (WKPI) are designed with measuring the productivity aspect, time, utility and quality. Improvement is done using the scale of priority that measured using importance performance analysis. The Improvements that suggested are including giving sign for items on each blocks, raw material warehouse layout improvement, create raw material checking form, material handling operator certification and raw material warehouse operator evaluation.